(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Classifying the malignancy of a renal tumour is one of the most important urological duties because it plays a key role in determining whether or not to undergo kidney removal surgery (nephrectomy). Currently, the radiological diagnostic made us89++ing computed tomography (CT) scans determines the likelihood of a tumour being malignant. However, it’s believed that up to 16 percent of nephrectomies may have been avoided since a postoperative histological study revealed that a tumour that had been first identified as malignant was actually benign. Numerous false-positive diagnoses lead to unnecessary nephrectomies, which increase the chance of post-procedural problems. In this article, we offer a computer-aided diagnostic method that analyses a CT scan to determine the tumour’s malignancy. The prediction, which is used to identify false-positive diagnoses, is carried out following radiological diagnosis. Our solution can complete this challenge with an F1 score of 0.84. Additionally, we suggest a cutting-edge method for knowledge transmission in the medical field using colorization-based pre-processing, which can raise the F1- score by as much as to 1.8.